(untitled) (JURNAL KEPERAWATAN, 2024)
Background : Stunting is a condition where a child experience growth disorders and the child’s height does not match his age. Early marriage is a legal marriage by someone who does not have the preparation and maturnity, causing several risk and major impacts, especially on health. Objective : This research aims to determine the relationship betwen young mothers’ knowledge level and the incidence of stunting in the working area of the Tilango Public Health Center working area. Methods This research is quantitative research with cross-sectional data. The sample includes mothers aged 10-20 years in the working area of the Tilango Public Health Center, totaling 35 respondets determined using the total sampling. Results : The study result showed that most mothers’ knowledge level is less knowledge, with 21 respondents (60%). Meanwhile, the incidence of stunting in the Short category was 18 respondents (51,4%). The statucal test result showed a p-value = 0,000 (p-value < 0,05). Conclusion : The conclusion is to determine the relationship between the young mothers’ knowledge level and the incidence of stunting in the Tilango Public Healt Center working area. Keywords: Knowledge; Mother; Stunting; Young